STRUCTURAL ORGANIZATION OF THE GALLBLADDER WALL GRAY GOOSE - Dubinin, S.I.; Ryabushko, E.B.; Улановська-Циба, Н.А.; Perederiy, N.A. (World of Medicine and Biology, 2014)
In this paper we studied the structural features of the gallbladder wall of gray geese in the comparative-anatomical aspect that can help in solving the problem of the prevention of gallstones and effective treatment of inflammatory processes in the organs of the hepatobiliary system. Structural diversity of the structure of the gallbladder wall, no doubt, can be attributed to the change in functional manifestations of the wall elements gall puzirya.
Keywords: gallbladder; cystic duct; cholecystitis; gall - stone disease